Características clínico-epidemiológicas de pacientes con síndrome de Guillain-Barré y COVID-19: Revisión Sistemática - Merino Ramírez, Junior Sleyter (2022)
There is evidence that SARS-CoV-2, the COVID-19 virus, is related as a predisposing factor or as a trigger with direct demyelinating pathophysiology in Guillain Barre Syndrome (GBS). Objective: To describe the clinical-epidemiological characteristics of patients with Guillain- Barre syndrome and COVID-19. Methods: Systematic review-type secondary research without meta-analysis (n=106), selected from 88 articles, where the clinical-epidemiological data were extracted, generating a database, percentages, averages, minimum and maximum values were calculated for the preparation of tables. Results: It occurred mainly in men, in patients with an average age of 52.94 years, it occurred within the first 10 days in 45.28%, the form of ascending presentation was the most common with 63.21%, as well as the AIDP variant in 55.66%, 29.25% required mechanical ventilation, with the most common comorbidity being hypertension (28.72%) and the most used treatment immunoglobulin IV (86.79%). Conclusion: GBS in COVID-19 occurs mainly in men, over 50 years of age, with the ascending, demyelinating variant being the most frequent, the use of immunoglobulin being the most frequent, and having a high recovery rate.